2007
DOI: 10.1016/j.wasman.2006.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Neutralization of an extremely acidic sludge and stabilization of heavy metals in flyash aggregates

Abstract: An extremely acidic, heavy metal-rich sludge (pH = À1.2) was scrubbed with a Class-F fly ash in order to simultaneously neutralize the acidity and stabilize the heavy metals contained in both wastes. This paper outlines the leaching behavior of the aggregate material generated by scrubbing. For proper fly ash/sludge ratios, the fly ash acted as an outstanding neutralizer for the acidic waste. Leaching of heavy metals from the aggregate samples was below the environmental limits within a pH range between 3 and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 18 publications
(15 reference statements)
0
10
0
1
Order By: Relevance
“…Alternatively, as the surface is negatively charged at basic pH, particles with a positive charge will be drawn to the surface of the FA. As it has been reported that the SrCO 3 particles have a positive zeta potential [18,46,47], it is suggested that this is the primary fixation pathway. The electrostatic interaction of the SrCO 3 particles with the FA surface is presented in Fig.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Alternatively, as the surface is negatively charged at basic pH, particles with a positive charge will be drawn to the surface of the FA. As it has been reported that the SrCO 3 particles have a positive zeta potential [18,46,47], it is suggested that this is the primary fixation pathway. The electrostatic interaction of the SrCO 3 particles with the FA surface is presented in Fig.…”
Section: Discussionmentioning
confidence: 95%
“…The possibility of using FA as an effective neutralization and fixation reagent for acidic wastes has been explored and suggested as a more significant economic value added as a utilization method [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Kanungo and Mohapatra [35] proposed a two-step hydrolysis process to explain the decrease of metal ion concentration in solution and relate it to the solubility constants. In addition to the physical adsorption and hydrolysis, Polat et al [36] suggested surface complexation of the metals to explain the metal adsorption in acidic solutions. Polat et al also proposed three consecutive processes for the metal removal for different pH regions.…”
Section: Heavy Metalsmentioning
confidence: 99%
“…The handling and disposal activity of NS are the costliest aspects of industrial wastewater treatment. Up to 60% of the total cost of the operation and maintenance of wastewater treatment plants is connected with sludge management [11]. Landfilling is considered to be the most appropriate choice for this sludge disposal at present [12], but it occupies large areas of land and wastes metal resources.…”
Section: Introductionmentioning
confidence: 99%